MIELITIS LUPUS SEBAGAI MANIFESTASI AWAL LUPUS ERITEMATOSUS SISTEMIK: LAPORAN KASUS - Erwin Widi Nugraha; Arthur H.P. Mawuntu; Riwanti Estiasari (Jurnal Sinaps, 2021)
Background: Lupus myelitis is one of 19 neuropsychiatric syndromes related to systemic lupus erythemathosus (SLE) defined by American College of Rheumatology (ACR) as neuro-psychiatric SLE (NPLSE). Lupus myelitis is one of the least common NPSLE with an incidence between 1-2% in the SLE population, however is generally severe. Almost 50% of cases of lupus myelitis are presented as the initial manifestation of SLE and about two-third is associated with high lupus activity. Case report: Twenty-three-year-old man presented with the only symptom of dysesthesia at epigastric and back region (T7 dermatome) with a sensation of tight band-like pain. Neurological examination revealed positive finger escape test and Hoffman-Tromner reflex on both hands, slight lower extremities weakness as demonstrated from repetitive squatting and tip-toe walking tests, and positive Lhermitte test. The whole non-contrast spine MRI found multiple short segment T2 hyperintensities on spinal cord level C6-C7 and T3-T5. The brain MRI result was unremarkable. The cerebrospinal fluid analysis only found a slight increase in protein level (50mg/dl). Laboratory results showed a positive anti-Smith (Sm) antibody and low level of vitamin D 25-OH total (20,6ng/ml). The patient was diagnosed with SLE and lupus myelitis. His lupus myelitis was presented as the initial and the only clinical manifestation of SLE. The heterogeneity of clinical manifestations of lupus myelitis poses a challenge in diagnosing this disorder, therefore immunological screening for SLE is essential and recommended in cases of myelitis.